Effectiveness Observation of Oral Motor Training Games in the Rehabilitation of Children with Articulation Disorders - Sun, Guang; Liu, Ying; Zhao, Jing; Song, Yinping; Jiang, Mingxia (Pacific International Journal, 2025)
Oral motor training games provide a novel reference for rehabilitation in children with articulation disorders. This study investigates the application effects of this method. Sixty children undergoing rehabilitation for articulation disorders were randomly divided into an observation group and a control group. The control group received conventional rehabilitation interventions, while the observation group incorporated oral motor training games into the baseline protocol. Comparisons were made between the two groups regarding improvements in oral motor function and speech abilities. Results demonstrated that the observation group exhibited significantly higher scores in both oral motor function and speech function compared to the control group (P < 0.05)23. Compared to conventional methods, oral motor training games show distinct advantages in enhancing articulation abilities, oral motor coordination, and speech outcomes for children with articulation disorders56. These findings suggest that oral motor training games can serve as a scientifically validated and effective rehabilitation intervention, offering valuable insights for clinical practice in articulation disorder management.